Strategi Mitigasi Risiko Supply Chain pada Industri Pakaian melalui Analisis SWOT dan House of Risk - Az-zahro', Sholihah; Kalista, Anggia (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
The clothing industry is one of the manufacturing sectors that is highly dependent on the smooth supply chain. Disruptions in the procurement, production, and distribution processes can pose various risks that have an impact on the efficiency and continuity of the company's operations. This study aims to identify the sources of risk in the supply chain of the clothing industry and formulate effective mitigation strategies. The qualitative approach was used through a case study on one of the clothing companies, with data collection techniques in the form of in-depth interviews, direct observations, and documentation studies. The analysis was carried out using the SWOT method to map internal and external factors, as well as the House of Risk (HOR) method to identify and prioritize risks and mitigation strategies. The results show that there are 17 risk events and 20 main risk agents that affect the company's supply chain. Based on the calculation of Aggregate Risk Potential (ARP) and effectiveness to hardship ratio (ETD), six priority mitigation strategies were obtained that can significantly reduce the impact of risk. The implementation of HOR-based mitigation strategies can help companies manage supply chain risks more sistematically and measurably, as well as increase competitiveness and operational sustainability amid market uncertainty.